ANALISIS KAPASITAS SALURAN DRAINASE JALAN MAYJEN HARUN SOHAR KOTA PAGAR ALAM - Remi Ayu Manda Sari; Lily Endah Diansari; Fameira Dhiniati (JURNAL ILMIAH BERING'S, 2021)
Drainage is a very important infrastructure for an area. Increasing population causes changes in land use resulting in reduced land infiltration and increased runoff. As happened in the drainage channel of Jalan Mayjen Harun Sohar in the rainy season. Drainage often overflowed and flooded people's homes. The purpose of this study is to analyze the capacity of drainage channels on Jalan Mayjen Harun Sohar Kota Pagar Alam. Calculation of Rainfall Intensity using the Mononobe equation. calculation of flood discharge plan based on the Rational method. Distribution of rainfall that is suitable in this study area is to use the gumbell method after being tested with the distribution match using the Chi-squared and Smirnov-Kolmogrov method with a planned rainfall Tr50 = 175.72 mm / hour, so the amount of existing Q = 3,563 m3 / sec and the magnitude of the planned flood discharge Q50 = 2,261 m3 / sec. It was concluded that the capacity of the drainage channel on Jalan Mayje Harun Sohar street was still able to accommodate the planned flood discharge but to avoid detention a dredging of 0.50 m was carried out